Floral biology and reproductive system of Passiflora mooreana (Passifloraceae) - Amela García, M.T. (1997)
Three floral phases were distinguished through anthesis, which starts after 1 p.m. Flowers in phase 1 and 3 (pollen donors) had their stigmas up. Flowers in phase 2 (receptors and donors of pollen) had their stigmas recurved near the anthers. Flowers in phase 2 occurred simultaneously with others in phase 1, during the day, and also with others in phase 3 (during the night). Sugar concentration in nectar varied: it was acceptable for Hymenoptera in the afternoon (when Xylocopa spp. and Centris spp. pollinate) and for sphingids after sunset (when Erinnyis ello seems to pollinate). Passiflora mooreana is melitophilous, but also is a resource for moths in the evening. Flowers showed a low degree of autoincompatibility. The low percent of fruits obtained suggests that the great distance between plants does not favor cross-pollination. The ovary wall may grow without pollination.